Sensitization of glutamate receptor‐mediated pain behaviour via nerve growth factor‐dependent phosphorylation of transient receptor potential V1 under inflammatory conditions. (20th July 2020) - Masuoka, Takayoshi; Yamashita, Yuka; Yoshida, Junko; Nakano, Katsuya; Tawa, Masashi; Nishio, Matomo; Ishibashi, Takaharu
Abstract : Background and Purpose: Glutamate and metabotropic glutamate (mGlu) receptors on primary sensory neurons are crucial in modulating pain sensitivity. However, it is unclear how inflammation affects mGlu receptor‐mediated nociceptive responses. We therefore investigated the effects of mGlu1/5 receptor agonists on pain‐related behaviour during persistent inflammation and their underlying mechanisms. Experimental Approach: Effects of a mGlu1/5 receptor agonist on pain‐related behaviour during inflammation was assessed in mice. Intracellular calcium responses, membrane current responses, and protein expression in primary sensory neurons were examined using cultured dorsal root ganglion (DRG) neurons, dissociated from wild‐type and gene knockout mice. Key Results: Persistent inflammation induced by complete Freund's adjuvant increased the duration of mGlu1/5 receptor‐mediated pain behaviour, which was antagonized by inhibition of nerve growth factor (NGF)–tropomyosin receptor kinase A (TrkA) signalling. Calcium imaging revealed that NGF treatment increased the number of cultured DRG neurons responding to mGlu1/5 receptor activation. Stimulation of mGlu1/5 receptors in NGF‐treated DRG neurons induced inward currents through TRPV1 channels in association with PLC but not with IP3 receptors. NGF treatment also increased the number of neurons responding to a DAG analogue via TRPV1 channel activation. Furthermore, NGF up‐regulated expression of TRPV1 and A‐kinase anchoring protein 5 (AKAP5), resulting in increased AKAP5‐dependent TRPV1 phosphorylation. AKAP5 knockout mice did not exhibit mGlu1/5 receptor‐mediated excitation in NGF‐treated DRG neurons or pain response facilitation under inflammatory conditions. Conclusions and Implications: NGF augments glutamate‐ and mGlu1/5 receptor‐mediated excitation of nociceptive neurons by AKAP5‐dependent phosphorylation of TRPV1 channels, potentiating hypersensitivity to glutamate in inflamed tissues. Abstract :